Assessment of a spodumene ore by advanced analytical and mass spectrometry techniques to determine its amenability to processing for the extraction of lithium. (April 2018) - Aylmore, Mark G.; Merigot, Kelly; Rickard, William D.A.; Evans, Noreen J.; McDonald, Bradley J.; Catovic, Enej; Spitalny, Peter
Highlights: Advanced analytical microscopy and mass spectrometry used to characterise pegmatite. Li is associated with spodumene with minor amounts of Li bearing micas and beryl. At P100  = 4 mm 90% of the spodumene recoverable with Li grades of 3.0–3.5wt% Minerals associated with Rb, Cs, Ta, Nb, Sn are liberated and recoverable. Mineralogical factors influencing the treatment of spodumene ore are discussed. Abstract: A combination of analytical microscopy and mass spectrometry techniques have been used to detect and characterise different lithium minerals in a LCT-Complex spodumene-type pegmatite from Pilgangoora located in the Pilbara region of Western Australia. Information collated by these techniques can be used to predict processing amenability. Samples were categorised into three subsamples (Pil1, Pil2, Pil3) based on colour and texture having different lithologies. The mineralogy and liberation characteristics of samples were characterised using automated mineralogy techniques and the Li content and elemental distribution within minerals defined using instrumentation with secondary mass spectrometry capabilities. The majority of lithium is associated with spodumene particles with minor amounts of lithium bearing micas and beryl in the Pil1 sample, whereas in Pil2 and Pil3 spodumene is largely the lithium source. In the Pil1 sample a proportion of spodumene particles have undergone alteration with spodumene being replaced by micaceous minerals of muscovite, lepidolite and trilithionite, as well as calcite. In Pil2 and Pil3 samples the spodumene particles are generally free of mineral impurities except minor intergrowths of quartz, feldspar and spodumene are evident in the coarser fractions. Based on mineralogical observations in the current study, the majority of the main gangue minerals quartz, K feldspar and albite can be rejected at a coarse grind size of −4 mm, to recover 90% of the spodumene with Li upgrade from 0.99–1.5 wt% Li to 3.0–3.5 wt% (6.5–7.5 wt% Li2 O). The iron content (81–1475 ppm) in the spodumene is low and therefore make these spodumene concentrates suitable for use in ceramic and glass applications. Recovery of spodumene in the coarse fractions could be improved by further particle size reduction to liberate spodumene from micas and feldspars in the middling class, which account for between 15 and 49% of the sample. However, the requirement to remove mineral impurities in the spodumene in downstream processing will be dependent on the method of processing as the presence of Li bearing micas, calcite and feldspar can be beneficial or detrimental to lithium recovery. The high content of Rb (1 wt%) and the abundance of free grains makes K feldspar a source of rubidium, particularly in the Pil3 sample which has K feldspar in high abundance (21 wt%) and can potentially be recovered by reverse flotation technique. The low concentrations of the Ta, Nb and Sn minerals identified in samples were found to be fairly well liberated and could be recovered by conventional gravity separation techniques.